Fungicidal Activities and Mechanisms of Action of Pseudomonas syringae pv. syringae Lipodepsipeptide Syringopeptins 22A and 25A - Bensaci, Mekki F.; Gurnev, Philip A.; Bezrukov, Sergey M.; Takemoto, Jon Y. (Frontiers in Microbiology, 2011)
The plant-associated bacterium Pseudomonas syringae pv. syringae simultaneously produces two classes of metabolites: the small cyclic lipodepsinonapeptides such as the syringomycins and the larger cyclic lipodepsipeptide syringopeptins SP22 or SP25. The syringomycins inhibit a broad spectrum of fungi (but particularly yeasts) by lipid-dependent membrane interaction. The syringopeptins are phytotoxic and inhibitory to Gram positive bacteria. In this study, the fungicidal activities of two major syringopeptins, SP22A and SP25A, and their mechanisms of action were investigated and compared to those of syringomycin E. SP22A and SP25A were observed to inhibit the fungal yeasts Saccharomyces cerevisiae and Candida albicans although less effectively than syringomycin E. S. cerevisiae mutants defective in ergosterol and sphingolipid biosyntheses were less susceptible to SP22A and SP25A but the relative inhibitory capabilities of SRE vs. SP22A and SP25A were maintained. Similar differences were observed for capabilities to cause cellular K+ and Ca2+ fluxes in S. cerevisiae. Interestingly, in phospholipid bilayers the syringopeptins are found to induce larger macroscopic ionic conductances than syringomycin E but form single channels with similar properties. These findings suggest that the syringopeptins target the yeast plasma membrane, and, like syringomycin E, employ a lipid-dependent channel forming mechanism of action. The differing degrees of growth inhibition by these lipodepsipeptides may be explained by differences in their hydrophobicity. The more hydrophobic SP22A and SP25A might interact more strongly with the yeast cell wall that would create a selective barrier for their incorporation into the plasma membrane.